ANALYSIS OF COVID TRANMISSION TO NURSES IN THE HOSPITAL (Al Insyirah International Scientific Conference on Health, 2021)
COVID-19 is still an outbreak that has not been resolved throughout the world. Nurses as one of the health workers who work at the forefront of health services are at risk of being exposed to COVID-19. Until now, the number of nurses who died as a result of exposure to COVID-19 has increased. This study aims to analyze the modes of transmission of COVID-19 in nurses. This type of research is quantitative research with analytic descriptive design. The number of respondents in the study was 31 nurses, which were obtained by using total sampling technique. The results of this study indicate that the transmission of COVID-19 to nurses occurs due to a history of contact with COVID-19 patients (80,6%), eating habits with colleagues (67,7%), treating patients with confirmed COVID-19 in a non-isolation room (67,7%), history of contact with hospital staff confirmed COVID-19 (51,6%), and visiting crowded places such as traditional markets (45,2%)
Keywords: Covid-19; Hospital; Nurses; Transmission